Fractional control of an offshore wind system - Melício, Rui (2019)
This paper presents a simulation on a way to improve the ability of an offshore wind system to recover from a fault in the rectifier converter. The system comprises a semi-submersible platform, a variable speed wind turbine, a synchronous generator with permanent magnets (PMSG), and a five-level multiple point diode clamped converter. The recovery is improved by shielding the DC link of the converter during the fault using as further equipment a redox vanadium flow battery. A fractional PI controller is used for the PMSG and the converter.